Comparatively Evolution and Expression Analysis of GRF Transcription Factor Genes in Seven Plant Species - Cheng, Zhihan; Wen, Shiqi; Wu, Yuke; Shang, Lina; Wu, Lin; Lyu, Dianqiu; Yu, Hongtao; Wang, Jichun; Jian, Hongju (Plants (Basel), 2023)
Growth regulatory factors (GRF) are plant-specific transcription factors that play pivotal roles in growth and various abiotic stresses regulation. However, adaptive evolution of GRF gene family in land plants are still being elucidated. Here, we performed the evolutionary and expression analysis of GRF gene family from seven representative species. Extensive phylogenetic analyses and gene structure analysis revealed that the number of genes, QLQ domain and WRC domain identified in higher plants was significantly greater than those identified in lower plants. Besides, dispersed duplication and WGD/segmental duplication effectively promoted expansion of the GRF gene family. The expression patterns of GRF gene family and target genes were found in multiple floral organs and abundant in actively growing tissues. They were also found to be particularly expressed in response to various abiotic stresses, with stress-related elements in promoters, implying potential roles in floral development and abiotic stress. Our analysis in GRF gene family interaction network indicated the similar results that GRFs resist to abiotic stresses with the cooperation of other transcription factors like GIFs. This study provides insights into evolution in the GRF gene family, together with expression patterns valuable for future functional researches of plant abiotic stress biology.